CREATION OF WEBSITE-BASED ELECTRONIC ARCHIVES AT THE CLASS II NON-TPI BLITAR IMMIGRATION OFFICE - W Wilonotomo; Galuh Boy Hertantyo; Fransiskus Vendyka Rozandya Putra (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
Information is important to facilitate administrative and bureaucratic work in the era of increasingly rapid technological development. Information from all recorded activities of institutions and agencies is stored in archive form. Arranging or managing the archives of applicants for passports and residence permits at the Immigration Office is the task of the Information Technology Subsection. It is known that currently Kantor Imigrasi Kelas II Non TPI Blitar is still using the conventional filing system, where for archiving it uses more paper, so there are lots of piles of archive files for passport and residence permit applicants that fill the archive room. The purpose of this research is to create a website- based Electronic Archive to reduce the risk of file accumulation in the archive room of Kantor Imigrasi Kelas II Non TPI Blitar. This study uses the System Development Life Cycle (SDLC) application development method which is a way of developing a software that provides the possibility to create a structured and systematic system (sequentially) starting at the stages of requirements analysis, system design, implementation, testing, development, and maintenance. The results of this research application "Arsip Elektronik Berbasis Website pada Kantor Imigrasi Kelas II Non TPI Blitar" has been successfully created using the SDLC design method. The existence of digitizing the archive files of applicants for passports and residence permits, will facilitate the archive search process and save the use of archive space at Kantor Imigrasi Kelas II Non TPI Blitar.